Ascites alone as the presentation of Congenital Tuberculosis - Purkait, S; Banerjee, P; Chatterjee, A; Pan, A (Journal of College of Medical Sciences-Nepal, 2015)
Congenital tuberculosis is a rare disease. It usually presents with respiratory distress, fever and organomegaly. We report a case of congenital tuberculosis presenting with ascites only. DOI: http://dx.doi.org/10.3126/jcmsn.v10i1.12766 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(1); 37-40